LPS induction of I kappa B-alpha degradation and iNOS expression in a skin dendritic cell line is prevented by the janus kinase 2 inhibitor, Tyrphostin b42 - Cruz, MT (2010)
The Janus kinase (JAK) family of protein tyrosine kinases are activated in response to a wide variety of external stimuli. Here we have investigated whether the janus kinase 2 (JAK2) is involved in the induction of nitric oxide synthase type II (iNOS) expression in a mouse fetal skin dendritic cell line (FSDC). In FSDC the expression of iNOS protein and nitric oxide production, in response to the lipopolysaccharide (LPS) stimulus (5 microg/ml), is inhibited by the specific inhibitor of the JAK2, tyrphostin B42 with an half maximal inhibitory concentration (IC(50)) of 9.65 microM. The antioxidant compound pyrrolidinedithiocarbamate (PDTC) inhibits both the nitrite production with an IC(50) of 16.6 microM and the iNOS protein expression in FSDC. In addition, LPS induces the activation of NF-kappa B, and tyrphostin B42 prevents the degradation of the cytosolic factor I kappa B-alpha and blocks the translocation of the NF-kappa B p65 protein subunit into the nucleus. These results indicate that the JAK family of protein kinases and the transcription factor NF-kappa B are involved in the induction of iNOS protein expression in FSDC stimulated with LPS.